Association between sleep quality and physical activity in postpartum women - Wu, Jiqiang (Sleep Health, 2019)
OBJECTIVE: To describe sleep quality and sleep duration in primiparous women six months postpartum and to determine whether sleep quality is associated with 24-hour physical activity assessed using tri-axial wrist accelerometry and a novel analytic technique, functional data analysis (FDA). METHODS: Six months postpartum, participants wore a tri-axial wrist accelerometer for 7 days and completed the Pittsburgh Sleep Quality Index (PSQI). We categorized sleep quality as good (score ≤ 5) or poor (> 5). Data were summarized as vector magnitude of accelerations net of local gravity, or “Euclidean Norm Minus One” (ENMO, mg), in 5 second epochs. Using FDA, we modeled ENMO as a continuously changing, functional outcome predicted by sleep quality. We also compared mean total ENMO per 24-hour day, mean minutes of moderate to vigorous physical activity (MVPA) and of light activity/day and mean minutes of MVPA in 10-minute bouts/day by sleep quality. RESULTS: Of 365 women that completed the PSQI, 215 (59%) reported poor sleep quality. 296 women completed both the PSQI and valid accelerometry. With the exception of one brief period around noon, sleep quality was not significantly associated with 24-hour physical activity according to FDA. Women with poor sleep quality had slightly greater total mean activity, minutes of light activity and minutes of MVPA per day, but no difference in minutes of MVPA in at least 10-minute bouts. CONCLUSION: Poor sleep quality is common 6 months postpartum. We identified no clinically significant differences in physical activity metrics between women with good and poor quality sleep.